General characteristics of anuran amphibians and their biodiversity / Características gerais dos anfíbios anuros e sua biodiversidade - Luan Lucas Cardoso Lima; João Pedro Silva Oliveira; Luiz Eduardo Bezerra Silva; Claudimary Bispo dos Santos (Universidade Estadual de Alagoas, 2019)
Anuran amphibians are vertebrates that have as singular characteristic the development of the larval phase in the aquatic environment and the adult phase in the terrestrial environment. Like other animals, they are components of the food chain, feeding on insects and other terrestrial invertebrates, ie, they are responsible for controlling various pests. In addition, they are also important indicators of environmental quality, being called bioindicators. The present study aimed to address the general characteristics of anuran amphibians and their biodiversity. The method was exploratory, through bibliographic research in the database of Scielo, CAPES and Google Scholar, as well as zoology books in the library of the State University of Alagoas. The following were selected to compose the present study: 10 international articles; 04 national articles; 06 international and 05 national informative sites; 07 national books and 09 international books, published from 1926 to 2017. From the literature review, it is possible to understand the importance of knowing the characteristics, behavior and role that anuran amphibians have in the ecological balance. It is noteworthy that the lack of knowledge of the population translates into the risk of extinction of the different species of these animals in the world. Thus, this study was relevant, in the sense of bringing clarification, allowing to revert a scenario of mistaken information about anuran amphibians.